Mid-term Results of Holmium Laser Enucleation of the Prostate (HoLEP) for the Treatment of Benign Prostatic Hyperplasia (BPH) by a Single Surgeon - Seong Choi (Kosin Medical Journal, 2013)
ObjectivesHere the author report the mid-term clinical outcomes analysis with efficacy and safety of HoLEP. MethodsFrom May 2010 to September 2012, 270 consecutive patients treated with HoLEP were enrolled in this study. All patients was evaluated by digital rectal examination (DRE), transrectal ultrasonography (TRUS), serum PSA preoperatively. International Prostate Symptom Score (IPSS), peak urinary flow rate (Qmax), and postvoid residual urine (PVR) were documented preoperatively and 1, 3, 6, 12, 24 months postoperatively. The perioperative data and complications were analyzed. All procedures of HoLEP was done by a single surgeon. ResultsThe mean patient age at the surgery was 67.5 years (45-82), and the mean PSA was 3.7 ng/mL (0.4-19.4). Mean operation time was 73.6 minutes (30-150). Mean prostate volume was 64.3 mL (20-150) and mean resected tisssue weight was 9.3 g (2-63). Mean catheter indwelling time was 2.7 day (1-6), and mean hospital stay was 3.2 day (1-7). The blood loss was minimal, so transfusion was not needed. The baseline data were IPSS; 23.0 (7-35), QoL score; 5.4 (4-6), Qmax (mL/s); 12.5 (1.2-16.5), PVR (mL); 59 (20-250). Postoperatively, IPSS and QoL scores and PVR decreased, and Qmax increased significantly. Intraoperative complication was minor capsular perforation (n = 5). Postoperative complications were acute urinary retention (n = 9), transient incontinence (n = 17), urinary tract infection (n=4), urethral stricture (n=4) and bladder neck contracture (n = 12). ConclusionsHoLEP showed statistical improvement of clinical parameters after 1 month operation and these results sustained for 24 months regardless of prostatic size.